Self-Regulation as a Response to Stress in Students during a Pandemic - Teguh Lesmana; Febryan Febryan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
It is undeniable, the danger of a pandemic has hampered human activities. So, to prevent the threat from this pandemic, the Indonesian government implemented Large-Scale Social Restrictions (PSBB) which also had an impact on the world of education with the implementation of online learning. Online learning during this pandemic poses several obstacles for students. These obstacles eventually cause students to experience stress. This study aims to determine the relationship between self-regulation and stress levels in Tangerang students during the pandemic. The method used is a quantitative method with a purposive sampling technique that uses a questionnaire for data collection. In this study, two questionnaires were used, namely the perceived stress scale to measure stress and the short form self-regulation questionnaire to measure self-regulation. Data were collected on 304 active student participants in the Tangerang area and analyzed using the Spearman's Rho correlation test. The results obtained from this study indicate that there is a significant negative relationship between self-regulation and student stress during the pandemic. A significant relationship can be seen from the p-value of 0.000 (p<0.05) and the r-value of -0.573. The r value indicates that the relationship between the two variables has a negative direction, meaning that the higher the self-regulation, the lower the stress. Good self-regulation that individuals have will be able to cope with stress in themselves. Tak dapat dipungkiri, bahaya dari pandemi telah membuat aktivitas manusia menjadi terhambat. Maka, untuk mencegah ancaman dari pandemi ini, pemerintah Indonesia menerapkan Pembatasan Sosial Berskala Besar (PSBB) yang berdampak pula pada dunia pendidikan dengan diberlakukannya pembelajaran daring. Pembelajaran daring di masa pandemi ini nyatanya menimbulkan beberapa hambatan bagi mahasiswa. Berbagai hambatan tersebut akhirnya menyebabkan mahasiswa mengalami stres. Penelitian ini bertujuan untuk mengetahui hubungan regulasi diri terhadap tingkat stres pada mahasiswa Tangerang di masa pandemi. Metode yang digunakan adalah metode kuantitatif dengan teknik purposive sampling yang menggunakan kuesioner untuk pengumpulan datanya. Dalam penelitian ini menggunakan dua kuesioner yaitu perceived stress scale untuk mengukur stres dan short form self-regulation questionnaire untuk mengukur regulasi diri. Pengambilan data dilakukan kepada 304 partisipan mahasiswa/i aktif di daerah Tangerang dan dianalisis menggunakan uji korelasional spearman’s rho. Hasil yang diperoleh dari penelitian ini menunjukkan bahwa terdapat hubungan negatif yang signifikan antara regulasi diri dengan stres mahasiswa di masa pandemi. Hubungan yang signifikan dilihat dari nilai p sebesar 0,000 (p<0,05) dan nilai r sebesar -0,573. Nilai r tersebut menunjukkan bahwa hubungan kedua variabel memiliki arah negatif, artinya semakin tinggi regulasi diri maka semakin rendah stres. Regulasi diri yang baik yang dimiliki individu akan mampu mengatasi stres dalam dirinyal